Novel gradient casting method provides high-throughput assessment of blended polyester poly(lactic-co-glycolic acid) thin films for parameter optimization - Venkatraman, Subbu S. (2017)
Pure polymer films cannot meet the diverse range of controlled release and material properties demanded for the fabrication of medical implants or other devices. Additives are added to modulate and optimize thin films for the desired qualities. To characterize the property trends that depend on additive concentration, an assay was designed which involved casting a single polyester poly(lactic-co-glycolic acid) (PLGA) film that blends a linear gradient of any PLGA-soluble additive desired. Four gradient PLGA films were produced by blending polyethylene glycol or the more hydrophobic polypropylene glycol. The films were made using a custom glass gradient maker in conjunction with a 180 cm film applicator. These films were characterized in terms of thickness, percent additive, total polymer (PLGA + additive), and controlled drug release using drug-like fluorescent molecules such as coumarin 6 (COU) or fluorescein diacetate (FDAc). Material properties of elongation and modulus were also accessed. Linear gradients of additives were readily generated, with phase separation being the limiting factor. Additive concentration had a Pearson’s correlation factor (R) of >0.93 with respect to the per cent total release after 30 days for all gradients characterized. Release of COU had a near zero-order release over the same time period, suggesting that coumarin analogs may be suitable for use in PLGA/polyethylene glycol or PLGA/polypropylene glycol matrices, with each having unique material properties while allowing tuneable drug release. The gradient casting method described has considerable potential in offering higher throughput for optimizing film or coating material properties for medical implants or other devices.